A significancia da densidade de drenagem para a analise geomorfologica. - Christofoletti, A. (My University, 1983)
Examines drainage density and networks in terms of methods of calculation, spatial and temporal variability, their relationship with hydrological basins and their paleoclimatic significance.-R.N.Gwynne
The significance of drainage density in geomorphological analysis